If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -24 = 58 + 4x Reorder the terms: -24 + 6x = 58 + 4x Solving -24 + 6x = 58 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -24 + 6x + -4x = 58 + 4x + -4x Combine like terms: 6x + -4x = 2x -24 + 2x = 58 + 4x + -4x Combine like terms: 4x + -4x = 0 -24 + 2x = 58 + 0 -24 + 2x = 58 Add '24' to each side of the equation. -24 + 24 + 2x = 58 + 24 Combine like terms: -24 + 24 = 0 0 + 2x = 58 + 24 2x = 58 + 24 Combine like terms: 58 + 24 = 82 2x = 82 Divide each side by '2'. x = 41 Simplifying x = 41
| 8X+7X+15=90 | | 13x-8y=180 | | .7x-3.4=.6x+2.1 | | 11=-10+7m | | 20=-6y+4(y+3) | | 32x-4(8x+4)=16 | | 11/6x^4 | | -4x=3x+7 | | 5x+4(7)=3 | | -1=2+-0.5y | | 8X+7X+15=180 | | 15=5(4-x)+10 | | x^2+y^2+10x-4y+29=4 | | 5(23-4y)+4y=3 | | 8w-w+8w= | | m^2+4m-12=-7 | | (24p^14xq^18)^1/2 | | -1=2+-0.5 | | 12/2118/x | | y=4*tan(x) | | -11x+4=24 | | 600=.75x-(650+.5x) | | (66+30)*x=360+30*x | | 6×1/4 | | 5/1=1/3 | | 27x=0 | | (66+30x)=360+30x | | 9/32/5 | | 3x+20+10x-21=90 | | -4x+9y=81 | | (-5-1)-2f=-2(3-5) | | (5x-7)(7x+9)=0 |